The Importance of State Defense Realization for the Young Generation in Building National Character - Rifan Apriantara; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno; Moch Yurianto; Surya Wiranto (Jurnal Kewarganegaraan, 2023)
Abstract Defending the Country is a concept that has long been known in Indonesia as an effort to build a strong national character and integrity. However, in its development, there are challenges for the younger generation to understand the true meaning of Defending the Country. This research was conducted with the aim of examining the importance of realizing State Defense for the younger generation through related literature studies. The research method used is a literature study by collecting data from journals, books and articles related to the concept of State Defense and the importance of the realization of State Defense for the younger generation. The results of the study show that the realization of State Defense has an important role in shaping quality national character, especially in the younger generation. Through the realization of Defending the Country, the younger generation can develop an attitude of patriotism, discipline, responsibility, courage and love for the nation and country. Families, schools and the government have an important role in providing education and opportunities for the younger generation to understand and apply the concept of Defending the Country in everyday life. Therefore, there is a need for more serious efforts from all parties in providing understanding and training regarding the importance of realizing the State Defense for the younger generation, in order to form a strong national character and integrity in the future. Keywords: State Defense, Young Generation, Realization, National Character